Resolutions and Decisions Adopted by the General Assembly During its Seventy-fifth Session: Volume III - United Nations Department for General Assembly; Conference Management (United Nations, 2021)
This is the official record of the resolutions and decisions adopted by the United Nations General Assembly during its seventy-fifth session. Supplement No. 49.